IDENTITAS VISUAL DIGITAL BRAND DALAM SOSIAL MEDIA: Sebuah Evaluasi Konsistensi Image dan Type Karya Mahasiswa dalam Mendesain Feed Instagram - Hananto, Brian Alvin (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2019)
With the rise of social media platforms within the past five years, the channel in which brands can interact with their users has also risen. A brand's communication to its user has become an essential thing to do in this 4.0 industry era. Instagram, which is one of the most used social media in Indonesia, is a medium that is full of visuals. The brand can communicate by creating a post that later can be accessed by its user. With an identified and consistent post, the branding process itself can be more informative and communicative. With three design samples that were made by students from the Visual Communication Design Department in Universitas Pelita Harapan, the author wants to show several things to make visual communication in Instagram consistent. By evaluating the design in basic graphic design terms, the author shows with the three samples that a graphic designer's role in visual communication within the 4.0 industry era has also become more crucial than before.